Freedom to Learn Independent Campus in the Eyes of the Progressive Philosophical School - Hani Irawati; Paidi Paidi (Jurnal Syntax Transformation, 2023)
Merdeka Belajar as one of the new policies in the education system in Indonesia needs to be critically and deeply analyzed from various aspects, one of which is analyzed from the perspective of philosophy. There are various philosophical schools used in the world of education, one of which is the philosophical school of progressivism. The purpose of writing this article is to look at the independent program of learning an independent campus from the lens of the philosophy of progersiveism. This paper is a literature study conducted by looking at various existing libraries. The independent learning program of an independent campus turned out to be very much in line with the spirit of the flow of progressivism.